NUTRIENT DIGESTIBILITY AND CAECUM MICROBIAL POPULATION OF BROILER FED CONOCARPUS LEAF MEAL DIETS - Al-qazzaz, M. F.; A. M. Humam; B. G. M. AL Khatib; H. A. AI- Mashhadani , H. A. AI- Mashhadani; O.A. Aljumaili; H. N. Ezzat, H. N. Ezzat (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The current study investigated the effect of Conocarpus erectus leaf meal on nutrient digestibility and cecal microbial quantification of broilers. A total of 48 Ross 308 chickens at 30 days old with similar body weights were randomly allocated into four treatments with 4 replicates of 3 birds each. The Conocarpus erectus leaf meal was supplemented to the basal diet at four levels (0%, 0.5%, 1%, and 2%). The diets were offered to the birds ad libitum for four days, after that the birds were slaughtered at 35 days old. Birds fed the diet containing 2 % Conocarpus erectus leaf meal reported significantly higher digestibility of crude protein, dry matter, and ash than other treatment diets. Also, crude fiber digestibility was increased significantly by 2% and 1% of Conocarpus erectus leaf meal. The digestibility of ether extract declined significantly by 0.5% Conocarpus erectus leaf meal. The number of Lactobacillus spp. was similar among birds fed dietary treatments. The 0.5% Conocarpus erectus leaf meal diet increased the number of Bifidobacterium spp. The lower number of E. coli spp was reported by the 2% Conocarpus erectus leaf meal. In conclusion, the Conocarpus erectus leaf meal has a potential nutritional value that can be used as feed additives in the broiler chicken diet.